Mindful Consumption: Utilising Instagram to Understand Influencer Marketing in the Digital Age - C. K, Karthika; P. Ravindranath, P. Ravindranath (Journal of Neonatal Surgery, 2025)
The significance of mindfulness in the digital age is increasing, as digital stimuli can elicit sensations of separation. Mindfulness entails complete concentration and awareness of thoughts, emotions, and surroundings devoid of judgemental biases. This study investigates the effects of exposure to influencer content on emotional well-being, self-esteem, body image, and disclosure practices in influencer marketing. A mixed-methods approach was employed, incorporating a questionnaire survey and semi-structured interviews with Instagram users in Kerala and Cochin. The study aims to assess the advantages of mindfulness as a mitigating element